Unspoken Connections: Exploring English Teachers’ Non-verbal Immediacy and Classroom Dynamics Through the Lens of Students - Fernandez, Jerald; Shienna Marie Caparas (Researchparks Publishing, 2025)
Non-verbal immediacy is a vital component of teacher-student interactions, particularly in English language classrooms, where it enhances communication and fosters student engagement. While non-verbal cues are commonly used by teachers in the Philippine context to aid comprehension, limited research exists on how students perceive these behaviors and their impact on classroom dynamics. This study explored students' perspectives on their English teachers' non-verbal immediacy and its potential effect on classroom interactions. Specifically, it examined the types of non-verbal behaviors students observe and how these behaviors affect their engagement, participation and the overall classroom dynamics. The study employed a qualitative phenomenological design, collecting data through semi-structured interviews with nine Grade 10 students from Balibago Integrated High School, Sta. Rosa City, Laguna. Thematic analysis followed Braun and Clarke’s framework. The findings identified eight superordinate themes and thirty-four subordinate themes, emphasizing the significant role of non-verbal behaviors—such as eye contact, hand gestures, facial expressions, and teacher movement—in enhancing student engagement and fostering a positive classroom environment. Eye contact and hand gestures particularly improve student focus and comprehension, while positive facial expressions, like smiling, reduce anxiety and create a supportive atmosphere. However, excessive eye contact and unclear gestures can lead to discomfort. Additionally, teacher tone, proximity, and posture play key roles in maintaining a participative classroom dynamic, with negative body language hindering engagement. The study concluded that non-verbal immediacy has a profound impact on classroom dynamics, highlighting its crucial role in enhancing student participation and creating an inclusive learning environment. The study recommended integrating non-verbal communication training into teacher development programs and encouraging educators to practice self-reflection, balance immediacy strategies, and adapt their behaviors based on student needs.